2019
DOI: 10.1177/0022022119837363
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Home Literacy Behaviors, Materials, Socioeconomic Status, and Early Literacy Outcomes Across 14 Low- and Middle-Income Countries

Abstract: Most research on reading acquisition is conducted in high-income countries, and the majority of the limited research from middle- and low-income countries focuses exclusively on school settings. We therefore know little about how home literacy environments (HLEs) relate to early reading skill acquisition in low-resource settings. This study uses baseline data from 18 Save the Children (SC) project sites across 14 countries in Central America, Asia, and Africa to address several questions. First, we examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 42 publications
3
34
0
2
Order By: Relevance
“…This implies that by providing more printed materials at home, parents may increase their children's opportunities to learn new words and this, in turn, can enhance their child's autonomy in accessing written materials as well as some active interest in learning new words (for a relevant discussion, see van Bergen et al, 2017). These findings, together with the findings of existing cross-cultural studies (Chiu et al, 2012;Arya et al, 2014;Araújo and Costa, 2015;Lenkeit et al, 2018;Zuilkowski et al, 2019), suggest that there might be value in revising the Home Literacy Model so that 'presence of reading materials at home, ' which can facilitate childdirected activities, is separated from the 'shared book reading' component and becomes part of a broader 'access to literacy resources' component.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This implies that by providing more printed materials at home, parents may increase their children's opportunities to learn new words and this, in turn, can enhance their child's autonomy in accessing written materials as well as some active interest in learning new words (for a relevant discussion, see van Bergen et al, 2017). These findings, together with the findings of existing cross-cultural studies (Chiu et al, 2012;Arya et al, 2014;Araújo and Costa, 2015;Lenkeit et al, 2018;Zuilkowski et al, 2019), suggest that there might be value in revising the Home Literacy Model so that 'presence of reading materials at home, ' which can facilitate childdirected activities, is separated from the 'shared book reading' component and becomes part of a broader 'access to literacy resources' component.…”
Section: Discussionmentioning
confidence: 94%
“…Niklas et al (2015) in turn found the associations between home-based literacy activities and children's verbal and cognitive abilities in English-speaking Australian and German children. Moreover, cross-cultural studies based on international survey data [e.g., Progress in International Reading Literacy Study (PIRLS); Program for International Student Assessment (PISA)] have consistently shown robust relationships between the amount of reading materials at home and children's early literacy skills across sociocultural contexts (Chiu et al, 2012;Arya et al, 2014;Araújo and Costa, 2015;Lenkeit et al, 2018;Zuilkowski et al, 2019).…”
Section: Cross-linguistic Studies On Hlementioning
confidence: 99%
See 2 more Smart Citations
“…Language issues are compounded in rural schools where learners have fewer opportunities to engage with science content and there is a lower probability that learners have a solid foundation in English that would allow them access to subject-related vocabulary and terminology. There can be systemic factors that negatively impact literacy development; for example, low family socioeconomic status (see Hemmerechts, Agirdag & Kavadias, 2017;Dowd, D'Sa, Noble, O'Grady, Pisani & Seiden, 2018;Zuilkowski, McCoy, Jonason & Dowd, 2019); poor education quality (see Harley, Woldie & von Gogh, 2019;Harris, Slate, Moore & Lunenburg, 2020) and a lack of available resources including African language use in published and online texts. In a South African context, the latter obstacle is exacerbated by the fact that South Africa has one of the highest linguistic diversities in the world with 11 official languages and many other indigenous languages that are not official, and the fact that a large percentage of rural English Second Language (ESL) learners have been shown to be "nonreaders in English".…”
Section: Language In Education and The Development Of Reading Comprehmentioning
confidence: 99%